Children of Single Fathers Created by Surrogacy: Psychosocial Adjustment Considerations and Implications for Research and Practice - Henrique Pereira (MDPI AG, 2022)
The existence of single-father families formed by surrogacy is becoming a more visible reality, even though this type of family organization is still perceived with stigma and negative attitudes by more traditional sectors of society, because it raises some concerns regarding the psychosocial well-being of children who are born into single-fathers' families via surrogacy, and in many cases, to gay single men who wish to become fathers. On the other hand, available research on the psychosocial well-being of these children is still very scarce and limited to a handful of Western countries. Hence, it is of utmost importance to examine studies that explore the psychosocial adjustment of these children. In this mini review, I show that all the studies revised demonstrate the good psychosocial adjustment of these children, and that they are as likely to flourish as children born into traditional families, even if they may find themselves exposed to prejudice and stigma. In conclusion, single fatherhood and surrogacy do not contribute to any adverse consequences to the children's psychosocial development and adjustment, and there is no observed evidence to why single men, irrespective of their sexual orientation, should not be fathers via surrogacy. Finally, implications for future research and interventions are also discussed.